Ternary precursor and preparation method thereof, ternary cathode material, lithium ion battery and electrical equipment

By designing a ternary precursor with a core, intermediate layer and shell in a high-nickel ternary positive electrode material, the problems of short battery life and poor rate performance of existing materials when the nickel content increases are solved, and higher electrochemical performance and cycling stability are achieved.

CN119774675APending Publication Date: 2025-04-08JINCHI ENERGY MATERIALS CO LTD +2
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510004138.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

When the nickel content of existing high-nickel ternary cathode materials increase, their energy density increases, but their battery life is short and their rate performance is poor, hindering market-oriented application.

Method used

A ternary precursor is provided, and its structure includes a core, an intermediate layer and a shell. The intermediate layer is a dense structure, the shell porosity is 8 to 30%, and the activity coefficient and crystallization coefficient are suitable. It is prepared by co-precipitation reaction.

Benefits of technology

In the lithium-ion battery, this ternary precursor enhances the stability of the internal structure of the positive electrode material, improves the charge and discharge cycle performance, and improves the electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774675A_ABST
    Figure CN119774675A_ABST
Patent Text Reader

Abstract

The present application provides a ternary precursor and a preparation method thereof, a ternary positive electrode material, a lithium ion battery and electrical equipment, and relates to the field of new energy technology. The ternary precursor provided in the present application includes a core, an intermediate layer and an outer shell, the intermediate layer is a dense structure, the outer shell is a high porosity structure, and the activity coefficient is 2.2 to 3.0, and the crystallization coefficient is 0.18 to 0.25. The use of the ternary precursor in the process of sintering with the lithium source can provide more transmission channels for lithium ions; at the same time, during the charge and discharge process, the resistance to lithium ion embedding and extraction is reduced, the lithium ion transmission distance is shortened, and the transmission rate is increased, which can effectively enhance the stability of the internal structure of the positive electrode material. During the charge and discharge cycle, the internal pores can relieve stress concentration and effectively improve the cracking inside the particles, thereby improving the capacity and cycle performance of the positive electrode material, and having superior electrochemical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new energy technology, and in particular to a ternary precursor and a preparation method thereof, a ternary positive electrode material, a lithium-ion battery and electrical equipment. Background Art

[0002] High-nickel ternary cathode materials have the advantage of high energy density. However, as the nickel content increases, the energy density is greatly improved, but the battery life is short and the rate performance is poor, which seriously hinders the market-scale application. The main reason is that the initial charge and discharge efficiency is low, and the lattice stress caused by the complex phase change caused by the lithium ion insertion and extraction during the cycle easily causes the cracks in the particles to initiate and expand, which eventually leads to particle crushing, weakened connection with the conductive agent, and increased impedance.

[0003] Existing high-nickel ternary positive electrode materials are mainly stabilized by doping metal or non-metal elements, such as Al, Zr, W and B, or by reducing the attack of the particle surface by the electrolyte through interface modification coating oxide, phosphide nanocoating, etc.; however, these methods are still insufficient to improve the electrochemical performance of high-nickel ternary positive electrode materials. Summary of the invention

[0004] The purpose of this application is to provide a ternary precursor and its preparation method, a ternary positive electrode material, a lithium-ion battery and electrical equipment, aiming to solve the problem that the existing high-nickel ternary positive electrode materials improve the material performance through pyrometallurgical doping and coating, but ignore the improvement of the electrochemical performance of the ternary precursor's structural characteristics, crystallinity and other properties.

[0005] To achieve the above objectives, the present application provides a ternary precursor, the ternary precursor comprises a core, an intermediate layer and an outer shell, the intermediate layer is a dense structure, the outer shell has a porosity of 8 to 30%; the activity coefficient (I 001 +I 101 ) / I 100 2.2~3.0, crystallization coefficient F 100 / (F 001 +F 101 )0.18~0.25.

[0006] In some embodiments, at least one of the following conditions is met:

[0007] A. The radial thickness ratio of the intermediate layer to the outer shell is (0.3-3):1;

[0008] B. The longest cross-sectional length of the core is 1 to 4 μm;

[0009] C. The cross-sectional area of ​​the core is 0.9 to 10 μm 2 ;

[0010] D. The porosity of the intermediate layer is 0 to 0.5%.

[0011] In some embodiments, at least one of the following conditions is met:

[0012] A. The ternary precursor is spherical or quasi-spherical;

[0013] B. When condition A is met, the average roundness of the particles of the ternary precursor is 1 to 1.5;

[0014] C. The median particle size D50 of the ternary precursor is 6 μm to 20 μm;

[0015] D. The tap density TD of the ternary precursor is 1.5 to 2.2 g / cm 3 ;

[0016] E. The specific surface area of ​​the ternary precursor is 6 to 21 m 2 / g;

[0017] F. The ternary precursor includes secondary particles composed of a plurality of primary particles, wherein the primary particles are in the shape of fine needles, laths or blocks;

[0018] G. When condition F is met, the primary particles have a length of 300 to 600 nm, a width of 50 to 290 nm, and a ratio of length to width of 1.3 to 4.5.

[0019] In some embodiments, the chemical formula of the ternary precursor is: Ni x Co y Mn z M 1-x-y-z (OH)2, wherein 0.6≤x≤0.98, 0≤y≤0.25, 0≤z≤0.3, x+y+z≤1, x, y and z are all molar percentages; M is one or more of Zr, Al, W, Ba, Y, Ca, and B.

[0020] The present application also provides a method for preparing the above-mentioned ternary precursor, comprising:

[0021] A metal salt solution containing at least nickel, cobalt and manganese, a precipitant and a complexing agent are introduced into the bottom liquid of a reaction kettle for coprecipitation reaction to obtain a slurry, which is then filtered, washed and dried to obtain the ternary precursor.

[0022] In some embodiments, at least one of the following conditions is met:

[0023] A. The flow rate of the metal salt solution is 1-12% / h of the reactor volume;

[0024] B. The precipitant flow rate is 20-38% of the metal salt solution flow rate;

[0025] C. The flow rate of the complexing agent is 5 to 20% of the flow rate of the metal salt solution;

[0026] D. The final solid content of the slurry is 250-650 g / L;

[0027] E. The coprecipitation reaction includes one or more reaction stages. When there are multiple reaction stages, the solution flow rate (L / h) of adjacent reaction stages gradually increases and the difference does not exceed 100%; the solid content growth rate per unit time in each reaction stage satisfies 2≤ΔM / ΔT≤12, wherein, Δ M is the solid content increase (g / L), Δ T is the corresponding time interval (h);

[0028] F. A surfactant may be introduced into the coprecipitation reaction process, wherein the surfactant is selected from one or more of oxalic acid, sodium pyrophosphate, polyvinyl pyrrolidone, and hexadecyltrimethylammonium bromide;

[0029] G. An oxygen-containing atmosphere may be introduced into the coprecipitation reaction process to make the oxygen content in the reactor 1% to 20% per volume percentage.

[0030] In some embodiments, at least one of the following conditions is met:

[0031] A. the total metal ion molar concentration of the metal salt solution is 1.0 to 2.5 mol / L;

[0032] B. The metal salt is selected from one or more of soluble sulfates, nitrates, and chlorides;

[0033] C. the precipitant is selected from sodium hydroxide and / or potassium hydroxide solution;

[0034] D. The mass percentage of the precipitant is 10 to 32%;

[0035] E. The complexing agent is selected from one or more of ammonia water, ammonium sulfate, and ammonium chloride; the mass percentage of the ammonia water is 10-21%;

[0036] F. The reactor bottom liquid comprises water, a precipitant and a complexing agent, or the reactor bottom liquid comprises water, seed crystals, a precipitant and a complexing agent, and the volume of water accounts for 20 to 80% of the volume of the reactor;

[0037] G. When condition F is met, the pH of the reactor bottom liquid is 11.00-12.20 or 9.7-10.80, the ammonia concentration is 2.0-6.5 g / L, and the oxygen content is less than 2.0%;

[0038] H. The pH of the coprecipitation reaction is 9.7 to 10.80, and the ammonia concentration is 2 to 5.5 g / L;

[0039] I. The coprecipitation reaction temperature is 40-80°C and the time is 25-50h.

[0040] The present application also provides a ternary positive electrode material, which is prepared from the above-mentioned ternary precursor.

[0041] The present application also provides a lithium-ion battery, comprising the above-mentioned ternary positive electrode material.

[0042] The present application also provides an electrical device, comprising the above-mentioned lithium-ion battery.

[0043] Compared with the prior art, the beneficial effects of this application include:

[0044] The ternary precursor provided in the present application includes a core, an intermediate layer and an outer shell. The intermediate layer is a dense structure, the outer shell is a high-porosity structure, and the activity coefficient and crystallization coefficient are appropriate. The use of the ternary precursor during sintering with a lithium source can provide more transmission channels for lithium ions; reduce the resistance to lithium ion embedding and extraction, shorten the lithium ion transmission distance, and effectively enhance the stability of the internal structure of the positive electrode material. During the charge and discharge cycle, the internal pores can relieve stress concentration and effectively improve the cracking inside the particles, thereby improving the capacity and cycle performance of the positive electrode material, and having excellent electrochemical properties.

[0045] The preparation method of the ternary precursor provided in the present application is flexible. In addition to conventionally controlling parameters such as complexing agent concentration, pH and temperature, additional measures such as atmosphere, surfactant and control of the solid content growth rate per adjacent unit time ([ΔM] / ΔT) are taken to obtain a ternary precursor with a suitable crystallization coefficient and activity coefficient. The ternary precursor includes a core, an intermediate layer and an outer shell, wherein the intermediate layer is a dense structure and the outer shell is a high-porosity structure. When the ternary precursor is mixed with a lithium source and sintered, the porous outer shell can reduce the lithium ion diffusion barrier, and the dense intermediate layer can play a supporting role to avoid structural collapse and cracking.

[0046] The ternary positive electrode material provided in the present application is prepared from the ternary precursor of the present application, and has high capacity and good cycle performance.

[0047] The lithium-ion battery and electrical equipment provided in this application adopt the positive electrode material of this application and have excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0049] Figure 1 This is a schematic diagram of the cross-sectional structure of the ternary precursor of the present application;

[0050] Figure 2 This is the SEM image of the ternary precursor of Example 1;

[0051] Figure 3 This is a cross-sectional view of the ternary precursor of Example 1;

[0052] Figure 4 This is a cross-sectional view of the ternary precursor of Example 2;

[0053] Figure 5 This is a cross-sectional view of the ternary precursor of Example 3;

[0054] Figure 6 This is a cross-sectional view of the ternary precursor of Example 4;

[0055] Figure 7 This is a cross-sectional view of the ternary precursor of Comparative Example 1;

[0056] Figure 8 This is a cross-sectional view of the ternary precursor of Comparative Example 2;

[0057] Fig. 9 This is a cross-sectional view of the ternary precursor of Comparative Example 3;

[0058] Fig.10 The XRD spectra of the ternary precursors of Examples 1 to 4 and Comparative Examples 1 to 3 are shown. DETAILED DESCRIPTION

[0059] As used herein:

[0060] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0061] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0062] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0063] In these examples, parts and percentages are by mass unless otherwise indicated.

[0064] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0065] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0066] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0067] The present application provides a ternary precursor, the structural schematic diagram of which is as follows Figure 1As shown, the ternary precursor includes a core region located at the core, a dense middle layer region covering the core region, and a high porosity shell region covering the dense middle layer region, the porosity of the shell is greater than the porosity of the core, the porosity of the shell is greater than the porosity of the middle layer, and the porosity of the shell is 8% to 30%, for example, it can be 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30% or any value between 8% and 30%. And the activity coefficient (I 001 +I 101 ) / I 100 is 2.2 to 3.0, for example, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0 or any value between 2.2 and 3.0, and the crystallization coefficient F 100 / (F 001 +F 101 ) is 0.18 to 0.25, for example, it can be 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25 or any value between 0.18 and 0.25.

[0068] Among them, (001), (100) and (101) are the crystal planes corresponding to 2θ=19.1±0.8°, 2θ=32.9±0.8° and 2θ=38.2±0.8° of the ternary precursor using Cu-Kα target X-ray diffraction; I 001 ,I 101 and I 100 are the diffraction intensities of the (001), (100) and (101) crystal planes, respectively, 100 、F 001 and F 101 are the half-peak widths of the (001), (100) and (101) crystal planes, respectively.

[0069] The ternary precursor provided in the present application includes a core, an intermediate layer and a shell, the intermediate layer is a dense structure, the shell is a high porosity structure, and the activity coefficient and crystallization coefficient are suitable. Using the ternary precursor in the process of sintering with the lithium source, the suitable activity coefficient ensures that the lithium source can be relatively fully diffused into the particles, and the crystallization coefficient ensures a relatively complete crystal structure, which can be inherited to the positive electrode material to the greatest extent as a skeleton; while taking into account the capacity and cycle performance, relatively good electrochemical performance can be achieved. The high porosity of the shell not only ensures that the ternary precursor has a higher specific surface area, but also makes it easier to fully contact and react with the lithium source. Secondly, it is more conducive to the growth and development of crystals under high temperature roasting, and reduces the side reactions caused by long-cycle contact with the electrolyte. The dense intermediate layer structure plays a supporting role to prevent cracking along the crystal due to the shrinkage factor of the high-temperature roasted particles. The kernel is generally equiaxed grains after high-temperature roasting, which can effectively enhance the stability of the internal structure of the positive electrode material. An overly large kernel weakens the radial arrangement of the primary particles, affects the lithium ion transmission path, and is not conducive to the performance of the rate performance. In short, ternary precursors with certain physical and chemical properties and specific structures can further improve the capacity and cycle performance of ternary positive electrode materials.

[0070] In some embodiments, the radial thickness ratio of the intermediate layer to the outer shell is (0.3-3):1, for example, it can be 0.3:1, 0.5:1, 0.8:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1 or any value between (0.3-3):1.

[0071] In some embodiments, the longest cross-sectional length of the inner core is 1 to 4 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm or any value between 1 and 4 μm.

[0072] If the core is too large, there will not be enough time for the middle layer and shell to grow. If the core is too large, there will be voids, which will affect the energy density. The thickness of the shell and the middle layer is controlled to make it easier for lithium ions to diffuse into the interior, avoiding the need for higher temperature sintering, which will also reduce capacity. The middle layer mainly plays a supporting role to avoid shrinkage and cracking, and it can also inhibit cracks from extending to the core.

[0073] In some embodiments, the cross-sectional area of ​​the core is 0.9-10 μm 2 , for example, it can be 0.9 μm 2 , 1μm 2 , 3μm 2 , 4μm 2 , 5μm 2 , 6μm 2 , 7μm 2 , 8μm 2 , 9μm 2 , 10μm 2 or 0.9~10μm 2Any value in between.

[0074] In some embodiments, the porosity of the middle layer is 0-0.5%, for example, it may be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5% or any value between 0-0.5%.

[0075] In some embodiments, the ternary precursor is a spherical or quasi-spherical particle; the average roundness of the particles of the ternary precursor is 1 to 1.5, for example, it can be 1, 1.1, 1.2, 1.3, 1.4, 1.5 or any value between 1 and 1.5. The roundness is defined as the ratio of the longest radius to the shortest radius of a single particle cross section, and the smaller the value, the higher the roundness.

[0076] In some embodiments, the median particle size D50 of the ternary precursor is 6 μm to 20 μm, and the tap density TD of the ternary precursor is 1.5 to 2.2 g / cm 3 ; The BET surface area of ​​the ternary precursor is 6 to 21 m 2 / g.

[0077] In some embodiments, the ternary precursor includes secondary particles composed of a plurality of primary particles, wherein the primary particles are in the shape of fine needles, laths, or blocks.

[0078] In some embodiments, the length of the primary particle is 300 to 600 nm, for example, it can be 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm or any value between 300 and 600 nm, the width is 50 to 290 nm, for example, it can be 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 290 nm or any value between 50 and 290 nm, and the ratio of length to width is 1.3 to 4.5, for example, it can be 1.3, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5 or any value between 1.3 and 4.5.

[0079] In some embodiments, the chemical formula of the ternary precursor is: Ni x Co y Mn z M 1-x-y-z (OH)2, wherein 0.6≤x≤0.98, 0≤y≤0.25, 0≤z≤0.3, x+y+z≤1, x, y and z are all molar percentages; M is one or more of Zr, Al, W, Ba, Y, Ca, and B.

[0080] The present application also provides a method for preparing the above-mentioned ternary precursor, comprising:

[0081] A metal salt solution containing at least nickel, cobalt and manganese, a precipitant and a complexing agent are introduced into the bottom liquid of a reaction kettle for coprecipitation reaction to obtain a slurry, which is then filtered, washed and dried to obtain the ternary precursor.

[0082] In some embodiments, the total metal ion molar concentration of the metal salt solution is 1.0-2.5 mol / L; the metal salt solution is selected from one or more of sulfate, nitrate, and acetate; and the flow rate of the metal salt solution is 1-12% / h of the reactor volume.

[0083] In some embodiments, the precipitant is selected from sodium hydroxide solution and / or potassium hydroxide solution; the mass percentage of the precipitant is 10-32%; and the flow rate of the precipitant is 20-38% of the flow rate of the metal salt solution.

[0084] In some embodiments, the complexing agent is selected from one or more of ammonia water, ammonium sulfate, and ammonium chloride; the mass percentage of ammonia water is 10-21%; and the flow rate of the complexing agent is 5-20% of the flow rate of the metal salt solution.

[0085] In some embodiments, the final solid content of the slurry is 250 g / L to 650 g / L, for example, it can be 250 g / L, 300 g / L, 350 g / L, 400 g / L, 450 g / L, 500 g / L, 550 g / L, 600 g / L, 650 g / L or any value between 250 and 650 g / L.

[0086] In some embodiments, the bottom liquid of the reaction kettle includes water, a precipitant and a complexing agent, or the bottom liquid of the reaction kettle includes water, a seed crystal, a precipitant and a complexing agent, and the volume of water accounts for 20 to 80% of the volume of the reaction kettle; when the bottom liquid of the reaction kettle includes water, a precipitant and a complexing agent, the pH of the bottom liquid of the reaction kettle is 11.0 to 12.2, for example, it can be 11.0, 11.1, 11.2, 11.3, 11.4, 11.5, 11.6, 11.7, 11.8, 11.9, 11.10, 11.1112, 11.12, 11.13, 11.14, 11.15, 11.16, 11.17, 11.18, 11.19, 11.20, 11.21, 11.22, 11.23, 11.24, 11.25, 11.26, 11.27, 11.28, 11.29, 11.30, 11.31, 11.32, 11.33, 11.34, 11.35, 11.36, 11.37, 11.38, 11.39, 11.40, 11.51, 11.52, 11.53, 11.54, 11.56, 11.57, 11.58, 11.59, 11.60, 11.61, 11.62, 11.63, 11.64, 11.65, 11.66, 1 .6, 11.7, 11.8, 11.9, 12.0, 12.1, 12.2 or any value between 11.0 and 12.2; when the reaction kettle bottom liquid includes water, seed crystals, precipitant and complexing agent; the pH value of the reaction kettle bottom liquid is 9.7 to 10.8, for example, it can be 9.7, 10.0, 10.2, 10.4, 10.5, 10.6, 10.8 or any value between 9.7 and 10.8.

[0087] In some embodiments, the ammonia concentration of the bottom liquid of the reactor is 2.0-6.5 g / L, for example, it can be 2.0 g / L, 2.5 g / L, 3.0 g / L, 3.5 g / L, 4.0 g / L, 4.5 g / L, 5.0 g / L, 5.5 g / L, 6.0 g / L, 6.5 g / L or any value between 2.0 and 6.5 g / L; the oxygen content is lower than 2.0%, for example, it can be 1.5%, 1.0% or any value lower than 2.0%.

[0088] In some embodiments, the coprecipitation reaction temperature is 40-80°C, for example, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or any value between 40-80°C; the reaction time is 25-50h, for example, 25h, 30h, 35h, 40h, 45h, 50h or any value between 25-50h; the pH is 9.7-10.8, for example, 9.7, 9.9. 8, 9.9, 10.1, 10.2, 10.3, 10.4, 10.5, 10.6, 10.7, 10.8 or any value between 9.7 and 10.8; the ammonia concentration is 2.0 to 5.5 g / L, for example, 2.0 g / L, 2.5 g / L, 3.0 g / L, 3.5 g / L, 4.0 g / L, 4.5 g / L, 5.0 g / L, 5.5 g / L or any value between 2.0 and 5.5 g / L.

[0089] In some embodiments, the coprecipitation reaction includes one or more reaction stages. When there are multiple reaction stages, the solution flow rate (L / h) of adjacent reaction stages gradually increases and the difference does not exceed 100%; the solid content growth rate per unit time in each reaction stage satisfies 2≤ΔM / ΔT≤12, for example, it can be 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 or any value between 2 and 12, wherein, Δ M is the solid content increase (g / L), Δ T is the corresponding time interval (h).

[0090] In some embodiments, a surfactant is also introduced during the coprecipitation reaction, and the surfactant is selected from one or more of oxalic acid, sodium pyrophosphate, polyvinyl pyrrolidone, and hexadecyltrimethylammonium bromide.

[0091] In some embodiments, an oxygen-containing atmosphere may be introduced into the coprecipitation reaction process so that the oxygen content in the reactor is 1% to 20% by volume, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 15%, 17%, 20% or any value between 1% and 20%.

[0092] The present application also provides a ternary positive electrode material, which is prepared from the above-mentioned ternary precursor.

[0093] The present application also provides a lithium-ion battery, comprising the above-mentioned ternary positive electrode material.

[0094] The present application also provides an electrical device, comprising the above-mentioned lithium-ion battery.

[0095] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0096] Example 1

[0097] The preparation method of the ternary precursor provided in this embodiment is as follows:

[0098] Step S1: According to the chemical formula Ni 0.90 Co 0.06 Mn 0.04 A mixed metal salt solution of nickel, cobalt and manganese sulfates with a total metal ion molar concentration of 2 mol / L is prepared according to the molar ratio of transition metal ions in (OH)2; a sodium hydroxide solution with a mass percentage of 32 wt.% is used as a precipitant; and ammonia water with a mass percentage of 21 wt.% is used as a complexing agent.

[0099] Step S2: Add 200L of pure water to a 300L reactor, control the temperature to 60°C, add ammonia water to adjust the ammonia concentration to 3.0g / L, add sodium hydroxide solution to raise the pH value of the bottom liquid in the reactor to 11.40, stir at 35Hz, introduce nitrogen into the reactor to make the oxygen concentration lower than 1.5%. Turn on the heating device to maintain the temperature in the reactor at 72°C.

[0100] Step S3: After the above conditions are prepared, the first stage (0-5min): the metal salt solution, sodium hydroxide and ammonia water are continuously introduced into the reactor at a flow rate of 3L / h, 1.1L / h and 0.06L / h respectively to carry out a coprecipitation reaction; the second stage (5min-7h): the metal salt solution 6L / h, the sodium hydroxide and ammonia water flow rates are 2.19L / h and 0.12L / h respectively into the reactor, and the solid content growth rate in adjacent unit time is 3.7-5.6g / L; the third stage (7-16h): the metal salt solution 9L / h, the sodium hydroxide and ammonia water flow rates are 2.19L / h and 0.12L / h respectively into the reactor. The water flow rate into the reactor is 3.3L / h and 0.18L / h, and the solid content increases by 5.6g / L in adjacent unit time; the fourth stage (16-24h): the metal salt solution is 12L / h, and the sodium hydroxide and ammonia flow rates are 4.38L / h and 0.24L / h, respectively, into the reactor, and the solid content increases by 7.4g / L in adjacent unit time; the fifth stage (24-end): the metal salt solution is 18L / h, and the sodium hydroxide and ammonia flow rates are 6.57L / h and 0.36L / h, respectively, into the reactor, and the solid content increases by 11.1g / L in adjacent unit time. During the entire reaction process, the ammonia concentration is maintained at 2-3.5g / L, and the pH is maintained at 10.40-10.65. When the particle size D50 reaches 13.5μm, the reaction is stopped, and the slurry obtained by the reaction is filtered, washed, dried, and sieved to obtain Ni 0.90 Co 0.06 Mn 0.04 (OH)2 nickel-cobalt-manganese ternary precursor, its SEM is as follows Figure 2 , cross section Figure 3 shown.

[0101] Example 2

[0102] Example 2 The preparation method is basically the same as that of Example 1, except that: in step S3, the surfactant hexadecyltrimethylammonium bromide solution is introduced into the second to fifth stages, and the flow rate of each stage is 0.1 L / h, 0.2 L / h, 0.3 L / h and 0.4 L / h respectively. When the particle size D50 reaches 13.5 μm, the reaction is stopped, and the slurry obtained by the reaction is filtered, washed, dried and sieved to obtain Ni 0.90 Co 0.06 Mn 0.04 (OH)2 nickel-cobalt-manganese ternary precursor, its cross-section is as follows Figure 4 shown.

[0103] Example 3

[0104] This embodiment first provides a ternary precursor, and the preparation method thereof is as follows:

[0105] Step S1: According to the chemical formula Ni 0.90 Co 0.06 Mn0.04 A mixed metal salt solution of nickel, cobalt and manganese sulfates with a total metal ion molar concentration of 2 mol / L is prepared according to the molar ratio of transition metal ions in (OH)2; a sodium hydroxide solution with a mass percentage of 32 wt.% is used as a precipitant; and ammonia water with a mass percentage of 21 wt.% is used as a complexing agent.

[0106] Step S2: Add 200L of pure water to a 300L reactor, control the temperature at 60°C, add ammonia water to adjust the ammonia concentration to 3.0g / L, add sodium hydroxide solution to raise the pH value of the bottom liquid in the reactor to 11.4, stir at 35Hz, and introduce nitrogen into the reactor to make the oxygen concentration lower than 1.5%.

[0107] Step S3: After the above conditions are prepared, the metal salt solution is at 18 L / h, the sodium hydroxide solution and the ammonia solution flow rates are 6.95 L / h and 0.38 L / h respectively, the ammonia concentration is controlled at 2.5-3.5 g / L, the pH is 10.50-10.80, and when the particle size grows to D V When the particle size reaches 50 to 3-4 μm, the addition of salt solution is stopped, and the obtained material is centrifuged, washed and dehydrated to obtain seeds.

[0108] Step S4: 200L of pure water is still added to the 300L reactor, and nitrogen is introduced during the process to protect the oxygen concentration in the reactor so that the oxygen concentration in the reactor is lower than 1.5%; 4.5kg of the seeds obtained in step S3 are also added to the reactor, stirred at 34Hz to fully disperse, and the heating equipment is turned on to maintain the temperature in the reactor at 72°C, and then a small amount of sodium hydroxide solution and an appropriate amount of ammonia water are added to the reactor to make its pH value reach 10.40-10.65 and the ammonia concentration 2-3.5g / L.

[0109] Step S5: After the above conditions are prepared, the first stage (0-3h): the metal salt solution, sodium hydroxide and ammonia water are continuously introduced into the reactor at a flow rate of 3L / h, 1.1L / h and 0.06L / h, respectively, to carry out a coprecipitation reaction; the second stage (3-7h): the metal salt solution, sodium hydroxide and ammonia water are respectively introduced into the reactor at a flow rate of 6L / h, 2.19L / h and 0.12L / h; the third stage (7-16h): the metal salt solution, sodium hydroxide and ammonia water are respectively introduced into the reactor at a flow rate of 9L / h, 3.3L / h and 0.18L / h; the fourth stage (16-24h): the metal salt solution, sodium hydroxide and ammonia water are respectively introduced into the reactor at a flow rate of 12L / h, 4.38L / h and 0.24L / h; the fifth stage (24-end): the metal salt solution, sodium hydroxide and ammonia water are respectively introduced into the reactor at a flow rate of 18L / h, 6.57L / h and 0.36L / h. The solid content growth rate per unit time in each stage was 2.6-2.8 g / L, 4.5-5.2 g / L, 5.5 g / L, 7.4 g / L and 11.1 g / L respectively. The ammonia concentration was maintained at 2-3.5 g / L throughout the reaction process, and the pH was maintained at 10.40-10.65. From the second to the fifth stage, the oxygen concentration was controlled between 3.5% and 5.5% by controlling the nitrogen and air introduced into the reactor, for example, 300 L / h of nitrogen and 82 L / h of air. The reaction was stopped when the particle size D50 reached 13.5 μm, and the slurry obtained by the reaction was filtered, washed, dried and sieved to obtain Ni 0.90 Co 0.06 Mn 0.04 (OH)2 nickel-cobalt-manganese ternary precursor, its cross section is as follows Figure 5 shown.

[0110] Example 4

[0111] Example 4 The preparation method is basically the same as that of Example 3, except that the surfactant hexadecyltrimethylammonium bromide solution is added to the first stage to the fifth stage in step S5, and the flow rate of each stage is 0.1L / h, 0.2L / h, 0.3L / h, 0.4L / h and 0.5L / h, respectively. Nitrogen protection is always used in the first stage to the fifth stage. When the particle size Dv50 reaches 13.5μm, the reaction is stopped, and the slurry obtained by the reaction is filtered, washed, dried and sieved to obtain Ni 0.90 Co 0.06 Mn 0.04 (OH)2 nickel-cobalt-manganese ternary precursor, its cross-section is as follows Figure 6 shown.

[0112] Comparative Example 1

[0113] Comparative Example 1 The preparation method is similar to that of Example 1, except that the multi-stage salt flow rate is adjusted to a constant flow rate of 21 L / h, and the flow rates of sodium hydroxide and ammonia water are 7.2 L / h and 0.42 L / h respectively. The ammonia concentration is maintained at 2-3.5 g / L and the pH is maintained at 10.40-10.65 during the entire reaction process. The reaction is stopped when the particle size D50 reaches 13.5 μm, and the slurry obtained by the reaction is filtered, washed, dried, and sieved to obtain Ni 0.90 Co 0.06 Mn 0.04 (OH)2 nickel-cobalt-manganese ternary precursor, its cross section is as follows Figure 7 shown.

[0114] Comparative Example 2

[0115] Comparative Example 2 The preparation method is similar to that of Example 3, and still maintains a high seed amount and multi-stage flow into the kettle to maintain high production efficiency. The only difference is that the entire reaction process is always protected by nitrogen, the ammonia concentration is always maintained at 2-3.5 g / L, and the pH is maintained at 10.40-10.65. When the particle size D50 reaches 13.5 μm, the reaction is stopped, and the slurry obtained by the reaction is filtered, washed, dried, and sieved to obtain Ni 0.90 Co 0.06 Mn 0.04 (OH)2 nickel-cobalt-manganese ternary precursor, its cross-section is as follows Figure 8 shown.

[0116] Comparative Example 3

[0117] Comparative Example 3 The preparation method is similar to that of Example 3, except that the multi-stage salt flow rate is adjusted to 21 L / h, and the sodium hydroxide and ammonia flow rates are 7.2 L / h and 0.42 L / h respectively. The ammonia concentration is maintained at 2-3.5 g / L and the pH is maintained at 10.40-10.65 during the entire reaction process. The reaction is stopped when the particle size D50 reaches 13.5 μm, and the slurry obtained by the reaction is filtered, washed, dried, and sieved to obtain Ni 0.90 Co 0.06 Mn 0.04 (OH)2 nickel-cobalt-manganese ternary precursor, its cross-section is as follows Fig. 9 shown.

[0118] The test method of the nickel-cobalt-manganese ternary precursor of each embodiment and comparative example is as follows:

[0119] The calculation of porosity and radial ratio requires sample pretreatment and imaging under a scanning electron microscope (SEM). Sample pretreatment, for example, can adopt argon ion polishing technology to remove the surface layer of the sample without stress and obtain an atomically clean surface. Further use of image processing software (MIPAR, Avizo and other software) can obtain the size information of each region. The porosity of different regions can be calculated by the cross-sectional porosity of a single particle = the pore area of ​​each region / the cross-sectional area of ​​each region × 100%). The porosity in this article is characterized by this method. The radial ratio refers to the thickness ratio of the dense area of ​​the intermediate layer and the high porosity area of ​​the outer shell in the radial (radial) direction.

[0120] Width and length measurement of primary particles: Image J software was used to measure the width and length of primary particles in the SEM image at a magnification of 10,000 times. The rule is as follows: the longest dimension of a single primary particle is considered its length, and the dimension measured perpendicular to the longest dimension is considered the width. A sufficient number of data were selected to calculate their average values ​​as the average width and average length of the primary particles.

[0121] Roundness: Use software to measure the spherical particles in the SEM image with a magnification of 100 times. Measure the ratio of the longest radius to the shortest radius of each particle*100%, select a sufficient number of data and calculate the average value as the final roundness.

[0122] Particle size test: The Malvern 2000 laser particle size analyzer, which is the mainstream in the industry, is used as the dispersant, pure water, and ultrasonic dispersion.

[0123] Tap density test: tested using Dandong Better BT-312 / 313 tap density meter.

[0124] The XRD patterns of the ternary precursors of Examples 1 to 4 and Comparative Examples 1 to 3 are as follows: Fig.10 shown.

[0125] The physical and chemical indicators of the ternary precursors of various embodiments and comparative examples are shown in Table 1.

[0126] Table 1 Physicochemical indicators of the ternary precursors of various embodiments and comparative examples

[0127]

[0128] Note: K 90 =(D 90 -D 10 ) / D 50 , K 95 =(D 95 -D5) / D 50 .

[0129] Electrochemical performance test

[0130] (1) Preparation of positive electrode material: The nickel-cobalt-based precursors of each embodiment and comparative example were mixed with lithium hydroxide monohydrate at a molar ratio of 1:1.04 in a high-speed mixer and mixed at 1000 rpm for 1 hour. The mixed materials were evenly spread and placed in a sagger and sintered at high temperature in a box furnace. The temperature of the first stage of the box furnace was set at 500°C and maintained for 5 hours; the second stage was set at 745°C and maintained for 15 hours, with an oxygen flow rate of 20 L / min; the corresponding positive electrode materials were obtained by cooling to room temperature in the furnace, crushing, and sieving 325 mesh.

[0131] (2) Button battery preparation and testing: The positive electrode materials obtained from each embodiment and comparative example were mixed into a uniform slurry in a ratio of positive electrode material: conductive agent: binder = 90:5:5 and N-methylpyrrolidone as a solvent, and coated on aluminum foil. The positive electrode sheet was obtained after drying, rolling and cutting; the negative electrode sheet used a metal lithium sheet. Then, a lithium battery was prepared in the order of positive electrode shell-positive electrode sheet-diaphragm-negative electrode sheet-stainless steel sheet-spring sheet-negative electrode shell. The electrolyte was 1 mol / L LiPF6 / EC:DMC (volume ratio of 1:1) with 10% (volume fraction) fluoroethylene carbonate (FEC) added. The diaphragm was a polypropylene microporous membrane. The button half-cells of embodiments 1 to 3 and comparative examples 1 to 2 were prepared respectively, and the electrochemical performance was tested at 2.8-4.30V.

[0132] The battery performance of each embodiment and comparative example is shown in Table 2.

[0133] Table 2 Electrochemical performance of each embodiment and comparative example

[0134]

[0135] According to Table 1 and Table 2, the activity coefficient is 2.2-3.0, the crystallization coefficient is 0.18-0.25, and the embodiments all show relatively high discharge capacity, especially embodiment 3 has a lower activity coefficient and crystallization coefficient, the highest discharge capacity, and a capacity retention rate of 87.3% after 70 cycles at 45°C, which is also relatively good. Comparative Example 2 has the highest activity coefficient, but the crystallization coefficient is low, and the discharge capacity is relatively low. By comparing Examples 1 to 4 with Comparative Example 1, it can be seen that even if the activity coefficient and crystallization coefficient remain the same, the difference in cross-sectional structure, especially the embodiment with a dense middle layer area and a high porosity loose outer shell area, has a higher discharge capacity and cycle retention rate. All embodiments and comparative examples are through coprecipitation reaction, by precipitating metal ions at a certain chelating agent concentration and pH conditions at a considerable precipitation rate. By controlling the solid content growth rate ([ΔM] / ΔT) of adjacent unit time and combining the atmosphere to control the cross-sectional characteristics, as much as possible, a structural feature with a dense middle layer and a high porosity outer shell is obtained.

[0136] In fact, the high-porosity shell material can quickly diffuse into the precursor due to the decomposed lithium source in the roasting stage, reducing the diffusion barrier of lithium ions and making it easier to exert capacity; the dense middle layer plays a supporting role, which can prevent the risk of structural collapse and cracking caused by high-temperature sintering. The structure with a denser surface layer, such as Comparative Examples 1 and 3, has a relatively small number of near-surface grain boundaries of the positive electrode material. Compared with Examples 1 to 4, the electrolyte can fully infiltrate the particle surface during activation, and even very little electrolyte can penetrate into the interior of the particle, shortening the lithium ion transmission distance. The pores left by the local shrinkage caused by high-temperature roasting of more porous samples can alleviate the lattice stress caused by the deintercalation of lithium ions during long-cycle charge and discharge, which causes cracks to initiate and expand, thereby further improving the cycle performance.

[0137] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0138] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A ternary precursor, characterized in that: The ternary precursor comprises a core, an intermediate layer covering the core and an outer shell covering the intermediate layer, wherein the intermediate layer is a dense structure and the outer shell has a porosity of 8 to 30%; the activity coefficient (I 001 +I 101 ) / I 100 The crystallization coefficient F is 2.2 to 3.

0. 100 / (F 001 +F 101 ) is 0.18~0.

25.

2. The ternary precursor according to claim 1, characterized in that: At least one of the following conditions is met: A. The radial thickness ratio of the intermediate layer to the outer shell is (0.3-3):1; B. The longest cross-sectional length of the core is 1 to 4 μm; C. The cross-sectional area of ​​the core is 0.9 to 10 μm 2 ; D. The porosity of the intermediate layer is 0 to 0.5%.

3. The ternary precursor according to claim 1, characterized in that At least one of the following conditions is met: A. The ternary precursor is spherical or quasi-spherical; B. When condition A is met, the average roundness of the ternary precursor particles is 1 to 1.5; C. The median particle size D50 of the ternary precursor is 6 μm to 20 μm; D. The tap density TD of the ternary precursor is 1.5 to 2.2 g / cm 3 ; E. The BET specific surface area of ​​the ternary precursor is 6 to 21 m 2 / g; F. The ternary precursor includes secondary particles composed of a plurality of primary particles, wherein the primary particles are in the shape of fine needles, laths or blocks; G. When condition F is satisfied, the length of the primary particle is 300 to 600 nm, the width is 50 to 290 nm, and the ratio of the length to the width is 1.3 to 4.

5.

4. The ternary precursor according to any one of claims 1 to 3, characterized in that: The ternary precursor chemical formula: Ni x Co y Mn z M 1-x-y-z (OH)2, wherein 0.6≤x≤0.98, 0≤y≤0.25, 0≤z≤0.3, x+y+z≤1, x, y and z are all molar percentages; M is one or more of Zr, Al, W, Ba, Y, Ca, and B.

5. A method for preparing a ternary precursor according to any one of claims 1 to 4, characterized in that: include: A metal salt solution containing at least nickel, cobalt and manganese, a precipitant and a complexing agent are introduced into the bottom liquid of a reaction kettle for coprecipitation reaction to obtain a slurry, which is then filtered, washed and dried to obtain the ternary precursor.

6. The method for preparing the ternary precursor according to claim 5, characterized in that: At least one of the following conditions is met: A. The flow rate of the metal salt solution is 1-12% / h of the reactor volume; B. The precipitant flow rate is 20-38% of the metal salt solution flow rate; C. The flow rate of the complexing agent is 5 to 20% of the flow rate of the metal salt solution; D. The final solid content of the slurry is 250-650 g / L; E. The coprecipitation reaction includes one or more reaction stages. When there are multiple reaction stages, the solution flow rates (L / h) of adjacent reaction stages gradually increase and the difference does not exceed 100%; The growth rate of solid content per unit time in each reaction stage satisfies 2≤ΔM / ΔT≤12, where: Δ M is the solid content increase (g / L), Δ T is the corresponding time interval (h); F. A surfactant may be introduced into the coprecipitation reaction process, wherein the surfactant is selected from one or more of oxalic acid, sodium pyrophosphate, polyvinyl pyrrolidone, and hexadecyltrimethylammonium bromide; G. An oxygen-containing atmosphere may be introduced into the coprecipitation reaction process to make the oxygen content in the reactor 1% to 20% per volume percentage.

7. The method for preparing a ternary precursor according to claim 5, characterized in that: At least one of the following conditions is met: A. the total metal ion molar concentration of the metal salt solution is 1.0 to 2.5 mol / L; B. the metal salt solution is selected from one or more of sulfate, nitrate and chloride; C. the precipitant is selected from sodium hydroxide solution and / or potassium hydroxide solution; D. The mass percentage of the precipitant is 10 to 32%; E. The complexing agent is selected from one or more of ammonia water, ammonium sulfate, and ammonium chloride; the mass percentage of the ammonia water is 10-21%; F. The reactor bottom liquid comprises water, a precipitant and a complexing agent, or the reactor bottom liquid comprises water, seed crystals, a precipitant and a complexing agent, and the volume of water accounts for 20 to 80% of the volume of the reactor; G. When condition F is met, the pH of the reactor bottom liquid is 11.0-12.2 or 9.7-10.8, the ammonia concentration is 2.0-6.5 g / L, and the oxygen content is less than 2.0%; H. The pH of the coprecipitation reaction is 9.7 to 10.8, and the ammonia concentration is 2.0 to 5.5 g / L; I. The coprecipitation reaction temperature is 40-80°C and the time is 25-50h.

8. A ternary positive electrode material, characterized in that: Prepared from the ternary precursor according to any one of claims 1 to 4.

9. A lithium ion battery, characterized in that: Including the ternary positive electrode material as described in claim 8.

10. An electrical equipment, characterized in that: Includes the lithium ion battery as claimed in claim 9.

Citation Information

Cited By

  • Hydroxide material as well as preparation method and application thereof

    CN121097032A

  • Precursor containing primary particles distributed along radial direction and preparation method and application thereof

    CN121394347A